Quantitative measurements of N‐linked glycoproteins in human plasma by SWATH‐MS. Issue 8 (11th March 2013) - Liu, Yansheng; Hüttenhain, Ruth; Surinova, Silvia; Gillet, Ludovic CJ; Mouritsen, Jeppe; Brunner, Roland; Navarro, Pedro; Aebersold, Ruedi; Figeys, Daniel
<x xml:space="preserve">Abstract</x> SWATH‐MS is a data‐independent acquisition method that generates, in a single measurement, a complete recording of the fragment ion spectra of all the analytes in a biological sample for which the precursor ions are within a predetermined m/z versus retention time window. To assess the performance and suitability of SWATH‐MS‐based protein quantification for clinical use, we compared SWATH‐MS and SRM‐MS‐based quantification of N‐linked glycoproteins in human plasma, a commonly used sample for biomarker discovery. Using dilution series of isotopically labeled heavy peptides representing biomarker candidates, the LOQ of SWATH‐MS was determined to reach 0.0456 fmol at peptide level by targeted data analysis, which corresponds to a concentration of 5–10 ng protein/mL in plasma, while SRM reached a peptide LOQ of 0.0152 fmol. Moreover, the quantification of endogenous glycoproteins using SWATH‐MS showed a high degree of reproducibility, with the mean CV of 14.90%, correlating well with SRM results (R2 = 0.9784). Overall, SWATH‐MS measurements showed a slightly lower sensitivity and a comparable reproducibility to state‐of‐the‐art SRM measurements for targeted quantification of the N‐glycosites in human blood. However, a significantly larger number of peptides can be quantified per analysis. We suggest that SWATH‐MS analysis combined with N‐glycoproteome enrichment in plasma samples is a promising integrative proteomic approach for biomarker discovery and verification.